Severe Salmonella Weltevreden Gastroenteritis Resistance Toward Conventional Antibiotics in an Infant: A Case Report. - Mohamad Qazreen Ahmad Shawaludin; Wai Bin Teh; Lee Ying Ting (Malaysian Journal of Paediatrics and Child Health, 2026)
Non-typhoidal Salmonella (NTS) infection is a common foodborne illness and remains a significant global health burden as a leading bacterial pathogen responsible for gastroenteritis. NTS typically causes self-limiting and uncomplicated gastroenteritis, particularly in children. Salmonella enterica serotype Weltevreden has been increasingly reported in outbreaks worldwide, including Southeast Asia. These outbreaks highlight the potential threat of NTS to human health, leading to high morbidity, mortality, and rising antimicrobial resistance. We report the case of a 3-month-old Indian boy with severe Salmonella serotype Weltevreden infection, resistant to conventional antimicrobial therapy. He presented with multiple episodes of non-bloody diarrhea, lethargy, and severe dehydration. Despite receiving intravenous Ampicillin and Ceftriaxone, his condition worsened with persistent diarrhea and fever, pancytopenia, and elevated C-reactive protein (CRP). His clinical and biochemical parameters eventually improved with treatment from the carbapenem class of antibiotics. This case underscores the severity of NTS infections in previously healthy infants, highlighting the critical role of appropriate antibiotic therapy and the growing concern of antimicrobial resistance in NTS infections.